2016
DOI: 10.1111/tmi.12712
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic differences in HIV/AIDS mortality in South Africa

Abstract: Abstractobjectives To quantify socio-economic differences in the risk of HIV/AIDS mortality in South Africa for different measures of socio-economic status.methods Systematic literature search in Web of Knowledge and PubMed. Measures of relative risk (RR) were pooled separately for education, income, assets score and employment status as measures of socio-economic status, using inverse-variance weighted DerSimonian-Laird random effects metaanalyses.results Ten studies were eligible for inclusion comprising ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…People having higher SES usually meant they possess more material (e.g., money, house), human (e.g., skills, knowledge), and social capital (e.g., social support, social network) compared to people with lower SES [5,35]. PLWHA with higher SES usually had lower mortality rate and better prognosis than their low-SES counterparts [3]. How the SES interacted with the association between HIV stigma and psychosocial problems was complex and required a more sophisticated study design to explore the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People having higher SES usually meant they possess more material (e.g., money, house), human (e.g., skills, knowledge), and social capital (e.g., social support, social network) compared to people with lower SES [5,35]. PLWHA with higher SES usually had lower mortality rate and better prognosis than their low-SES counterparts [3]. How the SES interacted with the association between HIV stigma and psychosocial problems was complex and required a more sophisticated study design to explore the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement and availability of HARRT, HIV/AIDS has transited from a lethal to a manageable chronic disease[1,2]. However, the prognosis differed significantly based upon PLWHA’s socio-economic status (SES) [3,4]. SES is a multi-dimensional and complex measure that has been defined variously in history, from a measurable to an abstract construct that reflects one’s access to collectively desired resources [5].…”
Section: Introductionmentioning
confidence: 99%
“…HIV risk is referring to HIV acquired through condom-unprotected sex under the influence of alcohol. Sources: Probst et al 3 , Probst et al 10 , Scott-Sheldon et al 17 , Ahmad et al 32 , Shisana et al 33 , Kehoe et al 36 , Statistics South Africa 44 . AAF, alcohol-attributable fraction; GISHA, Global Information System on Alcohol and Health; SABSSM, South African National HIV Prevalence, Incidence and Behaviour Survey; SES, socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
“…Persons of low SES were shown to have a higher HIV prevalence, 2 and an at least 1.5 times higher risk of dying from HIV/AIDS compared with persons of high SES. 3 With a Gini index over 60, South Africa is among the countries worldwide where income is most unequally distributed. 4 Not least due to the history of colonialism and apartheid, socioeconomic differences in South Africa are heavily intertwined with race and despite decreasing trends, the average income of a white person is still over 10 times that of a black African person.…”
Section: Introductionmentioning
confidence: 99%
“…Probst et al 22 performed a meta-analysis in order to ascertain the influence of socioeconomic status on the HIV mortality rate in South Africa and observed that lowincome individuals had a 50% higher chance of dying from HIV infection than people with a better economic status. Thus, people receiving a low income constantly deal with limited resources, which may negatively interfere with self-care of the disease.…”
mentioning
confidence: 99%